Factors Relating to Hope for Schizophrenia Survivors - Muhammad Iqbal Martani; Iyus Yosep; Efri Widianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the factors that influence hope in schizophrenia survivors at the Bumi Kaheman Rehabilitation Center. The method used is a quantitative approach with a cross-sectional study. The results of the study show that the factors that influence hope in schizophrenia survivors at the Bumi Kaheman Rehabilitation Center are social support, anxiety, recovery, and quality of life. This is shown by the p value of the relationship between hope and social support, anxiety, recovery, and quality of life which is less than 0.05. Hope is important in improving the care process carried out by schizophrenia survivors. Efforts to increase hope can be done by providing interventions that focus on the factors that affect hope. In conclusion, the factors that affect hope in schizophrenic patients consist of social support, anxiety, recovery, and quality of life. Keywords: Factors, Hope, Schizophrenia